Molecular mechanism of tRNA modification enzymes in bacterial pathogenicity and their development in antibiotic resistance - Swati Dixit (My University, 2025)
Antibiotic resistance is a global challenge still prevailing in many parts. While recent advancements in research and technology are helping to combat the challenge, some undermined and unexplored molecular factors of bacteria are interfering with the broad spectrum targeting of the pathogenicity. tRNA modifications and their enzymes are critical components of the bacterial regulatory mechanism and translation apparatus but their importance in the therapeutics of antibiotic resistance in bacterial human diseases has been elusive. Various tRNA modifications, along with their associated modifying enzymes, are integral to bacterial survival, particularly under adverse environmental conditions. Bacterial tRNA molecule exhibits diversity in modifications, while they are mainly concentrated at tRNA core and anticodon-loop (ACL) regions. This review examines the tRNA modifications in bacteria, including their influence on tRNA stability, protein translation, and their critical involvement in pathogenicity and virulence, encompassing processes such as cell cycle regulation, toxin production, outer membrane protein synthesis, and oxidative stress response. This review also emphasizes emerging strategies and challenges in targeting tRNA-modifying enzymes exclusive to pathogenicity in bacteria paving the foundation for antimicrobial resistance.
Keywords: tRNA modifications; pathogenicity; antimicrobial resistance; LC-MS; m1G37; RNA-seq